Numerical modeling​ and simulation of pitched and curved-roof solar greenhouses provided with internal heating systems for different ambient conditions. (February 2020) - Carlini, Maurizio; Castellucci, Sonia; Mennuni, Andrea; Morelli, Stefano
Abstract: During the past few years, the plant nursery sector has drastically minimized its carbon footprint by using geothermal systems for heating rather than fossil fuel. This study aims to define the temperature range inside a greenhouse by means of a multiparametric analysis, with regard to several inner and external conditions imposed. In detail, it has been used the Finite Element Method (FEM), contained in the modules for the thermal analysis of the COMSOL Multiphysics (CM) software. The greenhouse structures considered are the most common in the north of Italy and Europe. Through the development of a stationary study, it has been possible to choose the suitable design solution for the heating standard required for both the floriculture and the horticulture. A 2D study of the transitory has been implemented with the intent to consider as influential factors the irradiation and the daily temperature throughout the year. The temperature trend over horizontal direction is investigated to detect any non-uniformity on the temperature distribution to which floriculture and horticulture plants are exposed. This study aims to be a starting point for the development of a system to be exploited during the design phase of these kind of greenhouses, to enhance the functioning relatively to inner and external conditions fluctuations, maximizing the thermal performance.